O Aspecto social do acesso e difusão do documento de arquivo para a promoção da cidadania - SILVA, Gisele Lima e (2023)
The research aimed to identify elements that evidence the social aspect of Archival and Dissemination of the Archive Document and its essential role in promoting citizenship in Brazil through access to information.The reflections around the topics addressed seek to demonstrate the need for professionals to update themselves in the face of new demands and informational needs of society.Based on the above objective, a bibliographic research was chosen in documents from the areas involved in the research;in order to identify the interdisciplinarity of the topics studied, and to understand the importance of adapting Archival Science to the social context in which it is inserted, in order to serve all its users.